(untitled) (Fiep Bulletin - online, 2014)
The present descriptive study aims at comparing emotional conditions (neuroticism levels) and quality of life and BMI of selected individuals from the Vale do Sinos Region, Rio Grande do Sul, Brazil. Participated in the study 585 subjects between 18 and 80 years old selected by convenience for this study. The ANOVA with Scheffe Post Hoc was used in the data analysis in order to detect differences among the variables. In order to assess BMI, in the height variable, a stadiometer with an accuracy of 0.1cm and body mass through Plenna digital scale to 100g were used. Quality of life was assessed through WHOQOL-100 and emotional conditions through the Adjustment, Emotional and Neuroticism Factorial Scale (Escala Fatorial de Ajustamento Emocional/Neuroticismo - EFN) , which assesses the factors vulnerability, psychosocial maladjustment, anxiety and depression. It was observed that eutrophic subjects, when compared to overweight ones, showed more satisfaction with their quality of life (G2) (p<.005). This result was also observed in subjects classified as obese (p<.05). Regarding the subjects’ satisfaction with their health (G4), the eutrophic ones reported more satisfaction than the overweight and obese ones (p<.01). Analyzing the subjects’ emotional conditions, it was verified that eutrophic subjects, when compared to overweight and obese ones, were less vulnerable (N1) (p<.001), and less depressive (N4) (p<.01). When compared to obese subjects, the eutrophic ones were less anxious (N3). It was concluded that, the lower the body mass related to height, the more satisfied subjects are with their health and quality of life. Conversely, as body mass increases, the tendency to vulnerability, anxiety and depression increases too.